Melbury Square - Eden, Dorothy (Coward-McCann, 1970)
Spanning the years from the pre-World War I period to the present, it tells the dramatic story of a great beauty, Maud Lucies, the reigning debutante of London's fashionable Melbury Square at a time when nothing was more important than the next ball. Already famous as the daughter and model of one of the leading portrait painters of the day, Maud waltzes through her first season as a favorite of the King himself, who monopolizes her at ball after ball. it is expected that she will conclude the season with a brilliant titled marriage- but it is not to be so. Both idolized and dominated by her flamboyant father, Maud finds her search for love and happiness thwarted at every turn.
36593
Keywords: Eden, Dorothy -- 1912-1982; Literary Fiction; Melbury Square